Preparation method and application of TiO2-loaded NiFe water electrolysis catalyst
By using TiO2 nanotubes containing oxygen vacancy as the substrate in electrolytic water hydrogen production technology, the TiO2-supported NiFe nanosheet electrocatalyst was prepared, which solved the problem of slow kinetics of the oxygen evolution reaction and poor catalyst stability, and achieved low cost , high-efficiency electrocatalytic effect.
Patent Information
- Application Number
- CN202211558845.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-06
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-12-06
AI Technical Summary
In the existing electrolytic hydrogen production technology, the kinetics of the oxygen evolution reaction and the poor stability of the catalyst, especially the high cost and scarcity of precious metal catalysts limit their industrial applications.
TiO2 nanotubes containing oxygen vacancy were used as substrates to prepare TiO2-supported NiFe nanosheet electrocatalysts by electrodeposition to improve the conductivity and stability of the catalyst.
Low overpotential, high active sites and good stability are achieved, significantly improving the electrocatalytic activity of oxygen evolution and reducing the cost of electricity conversion during the electrolysis process.
Smart Images

Figure CN115747871B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of water electrolysis hydrogen production catalysts and relates to a preparation method of a TiO2-loaded NiFe oxygen evolution catalyst and application thereof in water electrolysis. Background Art
[0002] The growing demand for energy and related environmental issues have driven the development of sustainable energy to replace fossil fuels. Hydrogen energy has become the most ideal clean energy source due to its high combustion calorific value, non-toxicity, and wide sources. The alkaline water electrolysis hydrogen production technology has easy operating conditions and low investment costs, and the technology is more mature, making it one of the most promising hydrogen production technologies. The overall water splitting consists of two half reactions, namely the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER). Both have technical problems such as slow kinetics and low catalyst stability. In particular, the oxygen evolution reaction requires greater energy consumption due to the transfer of four electrons. At present, precious metals and their oxides (Pt, RuO2 and IrO2) are the most effective catalysts, but their high prices and scarcity have greatly limited their large-scale industrial applications. Therefore, it is crucial to develop low-cost and high-efficiency OER catalysts to significantly reduce their overpotential and improve the power conversion efficiency in the water electrolysis process.
[0003] So far, people have been committed to exploring efficient and stable OER and its electrocatalysts, such as transition metal oxides / hydroxides, sulfides, phosphides, selenides and nitrides. If transition metal catalysts are supported on conductive substrates, such as porous carbon and metal foams, the conductivity of the electrocatalyst can be improved. However, these carbon or metal foam supports are easily electrochemically oxidized, especially under oxidative OER reactions. Metal oxide supports are more stable and resistant to electrochemical oxidation, providing strong metal-support interactions for nanocatalysts, and are therefore considered to be promising substrates in heterogeneous catalysis. TiO2 has good chemical stability in both alkaline and acidic conduction and is a widely used catalyst support. However, the low conductivity of TiO2 supports hinders the required effective electron transport and limits the activity of the corresponding electrocatalysts. The introduction of oxygen vacancies (OV) can improve the conductivity of metal oxides, and can also strengthen the metal-support interaction and improve the stability of supported nanocatalysts. On the other hand, metal-based materials, such as NiFe alloys, NiFe hydroxides, metal phosphides, metal sulfides, etc., have been widely reported as efficient electrocatalysts in alkaline solution electrolysis. For example, the patent: A method for preparing Mg-doped NiFe-based (oxy)hydroxide and its oxygen evolution electrocatalytic application (202210732750.2). This scheme uses foam iron as the substrate to load nickel iron. Since the metal foam carrier is easily electrochemically oxidized, especially in the oxidative OER reaction, it affects the stability and conductivity of the catalyst. Summary of the invention
[0004] The purpose of the present invention is to address the problem that the catalytic activity and stability of NiFe-based electrocatalysts need to be further improved, and to propose a method for preparing a TiO2-loaded NiFe nanosheet electrocatalyst and its application. The method uses TiO2 nanotubes containing oxygen vacancies as a substrate, that is, firstly anodizing a titanium mesh to obtain TiO2 nanotubes, and then heating and calcining the nanotubes in a hydrogen / argon atmosphere to obtain TiO2 nanotubes containing oxygen vacancies. The present invention is used for electrocatalytic oxygen evolution reaction, and has the advantages of low OER overpotential, more catalytic active sites, better oxygen evolution electrocatalytic activity, etc., and at the same time, it shows excellent stability under continuous operation, and has broad application prospects in the energy industry in the future.
[0005] The technical solution of the present invention is:
[0006] A method for preparing a TiO2-loaded NiFe water electrolysis catalyst, the method comprising the following steps:
[0007] (1) Treatment of titanium mesh:
[0008] Select a two-electrode system, with a pretreated titanium mesh as the working electrode and a carbon rod as the counter electrode, insert them into the electrolyte, keep the voltage constant at 15-25V, and keep the time at 1-5h;
[0009] The electrolyzed titanium mesh is heated to 450-500° C. in a mixed atmosphere and calcined for 1-3 hours to obtain a titanium mesh having TiO2 nanotubes containing oxygen vacancies grown on the surface;
[0010] The electrolyte is composed of: 10-20 mL of deionized water and 80-90 mL of (CH2OH)2 are added to every 1 g of NH4F;
[0011] The mixed atmosphere is hydrogen and argon; the volume ratio of the two is 5:95;
[0012] The pretreatment of the titanium mesh is as follows: placing the titanium mesh in C3H6O, C2H5OH and deionized water in turn, and ultrasonically cleaning them for 10-30 minutes respectively;
[0013] (2) In a three-electrode system, a titanium mesh with TiO2 nanotubes containing oxygen vacancies grown on the surface is used as a working electrode, a carbon rod is used as a counter electrode, and a saturated calomel electrode is used as a reference electrode. The titanium mesh is immersed in an electroplating solution and deposited at a constant current of -2 to -20 mA for 10 to 60 minutes; then washed and dried to obtain a TiO2-loaded NiFe nanosheet electrocatalyst;
[0014] The solutes of the electroplating solution are NiCl2·6H2O and FeCl3·6H2O, the molar ratio of Ni:Fe is 1:0.5-1.5; the total metal concentration of the electroplating solution is 0.1-0.15 mol / L;
[0015] The TiO2-loaded NiFe water electrolysis catalyst prepared by the method is used for electrocatalytic oxygen evolution reaction.
[0016] All the raw materials involved were purchased commercially.
[0017] The essential features of the present invention are:
[0018] The present invention uses TiO2 nanotubes containing oxygen vacancies as a substrate and designs a NiFe-based electrocatalyst with a nanostructure by an electrodeposition method. The introduction of oxygen vacancies (OVs) can improve the conductivity of metal oxides, strengthen the metal-carrier interaction, and improve the stability of supported nanocatalysts. The nanostructure can increase the specific surface area of the catalyst, provide more active sites, and enhance the electron transfer in the electrocatalytic process.
[0019] The beneficial effects of the present invention are:
[0020] 1) The nanostructure of the catalyst provides abundant mass transfer channels, increases active sites, and facilitates gas diffusion and electrolyte transport.
[0021] 2) Metal oxide supports have good stability and resistance to electrochemical oxidation. The introduction of oxygen vacancies (OVs) can also improve the conductivity of metal oxides, strengthen the interaction between metals and supports, and enhance the stability of supported nanocatalysts.
[0022] 3) Combining NiFe-based materials with conductive substrates to construct two-dimensional electrocatalysts can enhance the conductivity of the catalyst.
[0023] 4) TiO2-loaded NiFe water electrolysis catalyst is prepared by electrodeposition at room temperature. Compared with traditional catalyst synthesis conditions, this method has the characteristics of mild reaction conditions. At the same time, the low current synthesis method involved is a low-consumption method for synthesizing catalysts, which further reduces the cost of catalyst preparation engineering.
[0024] 5) The linear scan of the oxygen evolution reaction can be seen at 100 mA cm -2 The NiFe@TiO2 catalyst exhibits an OER overpotential of 300 mV, which is much lower than the commercial Ir / C (450 mV). In the overall water electrolysis reaction, the electrode only needs a potential of 1.83 V to achieve 100 mA cm -2 It has a current density of 100 kWh and exhibits excellent stability under 100 h of continuous operation, and has broad application prospects in the energy industry in the future. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1This is the SEM image of NiFe@TiO2 prepared in Example 1.
[0026] Figure 2 This is the TEM image of NiFe@TiO2 prepared in Example 1.
[0027] Figure 3 Linear scan (LSV) diagram of the oxygen evolution reaction (OER) of NiFe@TiO2, Ni@TiO2 and TiO2, and commercial Ir / C obtained in Examples 1 and 2 in alkaline electrolyte.
[0028] Figure 4 Linear scan (LSV) diagram of oxygen evolution reaction (OER) of NiFe@TiO2, TiO2 and commercial Ir / C in alkaline electrolyte under different electroplating conditions (different current density and electroplating time) of Examples 1 and 3 to 5.
[0029] Figure 5 The NiFe@TiO2 prepared in Example 1 is 100mAcm -2 After 50 hours of long-term durability test under current density of . DETAILED DESCRIPTION
[0030] The present invention is described in detail below through specific embodiments, but the protection scope of the present invention is not limited thereto.
[0031] Embodiment 1:
[0032] (1) Preparation of TiO2 nanotubes: In order to remove impurities on the surface of the titanium mesh, the titanium mesh (10mm×35mm, 120 mesh) was placed in C3H6O, C2H5OH and deionized water respectively, and each was ultrasonically cleaned for 10-30 minutes. 1g NH4F was added to 10mL deionized water and stirred to dissolve. 90mL (CH2OH)2 was added to the solution and stirred evenly. A two-electrode system was selected, with the titanium mesh as the working electrode and the carbon rod as the counter electrode. The titanium mesh was placed in the prepared solution for anodization at a constant voltage of 20V for 3 hours. After oxidation, the titanium mesh was rinsed with deionized water, placed in an oven for drying and then taken out. The temperature was raised from room temperature to 450℃ in 5% H2 / Ar (H2 volume: Ar volume = 5:95) gas, kept warm for 2 hours, and naturally cooled to room temperature. The titanium mesh with oxygen vacancies TiO2 nanotubes grown on the surface was obtained. Under thermal conditions, hydrogen atoms interact with lattice oxygen on the titanium dioxide surface to form oxygen vacancies, thereby obtaining TiO2 nanotubes containing oxygen vacancies.
[0033] (2) 1.1885 g NiCl2·6H2O (0.005 mol) and 1.351 g FeCl3·6H2O (0.005 mol) were added to 100 mL deionized water and stirred to dissolve to obtain an electroplating solution; the titanium mesh containing oxygen vacancy TiO2 nanotubes treated in step (1) was used as a working electrode, a carbon rod was used as a counter electrode, and a saturated calomel electrode was used as a reference electrode. The titanium mesh was immersed in the electroplating solution for electroplating, and constant current deposition was performed at -20 mA for 15 min. The titanium mesh was then rinsed with deionized water, placed in an oven for drying, and then taken out to obtain a TiO2-loaded NiFe-based electrocatalyst, which was recorded as NiFe@TiO2-1.
[0034] The NiFe@TiO2 prepared in Example 1 was characterized by TEM, SEM and other characterization methods. The microstructure of the electrocatalyst was studied by scanning electron microscopy (SEM, Quanta450FEG) and TEM (JEOL2010F). In a standard three-electrode system, the electrolysis reaction was measured using a CHI760E electrochemical workstation, in which NiFe@TiO2 was used as the working electrode, a carbon rod was used as the counter electrode, a saturated calomel electrode (SCE) was used as the reference electrode, and the electrolyte was 1 molKOH. The detection range of the linear sweep voltammetry (LSV) curve was 0-1V (relative to saturated calomel), and the scanning speed was 10mVs -1 According to E RHE =E SCE +0.0591×pH+0.241 to convert the potential to reversible hydrogen electrode (RHE).
[0035] pass Figure 1 and Figure 2 The SEM and TEM images show that the prepared NiFe@TiO2 is a nanostructure, which increases the active surface area of the catalyst. The electrochemical active surface area of NiFe@TiO2 is 213.5 cm -2 , which is more conducive to the oxygen evolution reaction.
[0036] Embodiment 2:
[0037] (1) Preparation of TiO2 nanotubes: refer to the method and preparation conditions of step (1) in Example 1.
[0038] (2) Add 2.377 g NiCl2·6H2O (0.01 mol) into 100 mL deionized water and stir to dissolve; use the titanium mesh as the working electrode, the carbon rod as the counter electrode, and the saturated calomel electrode as the reference electrode. Immerse the titanium mesh treated in step (1) in the mixture and perform electroplating at a constant current of 2 mA for 30 min. Rinse the titanium mesh with deionized water, put it in an oven for drying, and then take it out to obtain a TiO2-loaded Ni-based electrocatalyst, which is recorded as Ni@TiO2.
[0039] Figure 3 The LSV curves of Examples 1 and 2 are linear sweep (LSV) curves of NiFe@TiO2, Ni@TiO2 and TiO2, and commercial Ir / C in alkaline electrolyte for oxygen evolution reaction (OER). It can be seen from the figure that under the premise of using TiO2 containing oxygen vacancies as the substrate, the performance of the Ni-based electrocatalyst (Example 2) is higher than that of the catalyst without electroplating, and the performance of the NiFe-based electrocatalyst (Example 1) is higher than that of the Ni-based electrocatalyst (Example 2). This shows that the synergistic effect between NiFe-based substances has a promoting effect on the electrocatalytic performance of the oxygen evolution reaction.
[0040] Embodiment 3:
[0041] (1) Preparation of TiO2 nanotubes: refer to the method and preparation conditions of step (1) in Example 1.
[0042] (2) Referring to the method and preparation conditions of step (2) in Example 1, the current density was reduced and the electroplating time was increased. Constant current deposition was performed at -10 mA for 30 min to obtain a TiO2-supported NiFe-based electrocatalyst, which was recorded as NiFe@TiO2-2.
[0043] Embodiment 4:
[0044] (1) Preparation of TiO2 nanotubes: refer to the method and preparation conditions of step (1) in Example 1.
[0045] (2) Referring to the method and preparation conditions of step (2) in Example 3, the electroplating time was increased again, and constant current deposition was performed at -10 mA for 60 min to obtain a TiO2-supported NiFe-based electrocatalyst, which was recorded as NiFe@TiO2-3.
[0046] Embodiment 5:
[0047] (1) Preparation of TiO2 nanotubes: refer to the method and preparation conditions of step (1) in Example 1.
[0048] (2) Referring to the method and preparation conditions of step (2) in Example 3, the current density was reduced again and constant current deposition was carried out at -5 mA for 30 min to obtain a TiO2-supported NiFe-based electrocatalyst, which was recorded as NiFe@TiO2-4.
[0049] Figure 4 The linear sweep (LSV) diagram of the oxygen evolution reaction (OER) of NiFe@TiO2, TiO2 and commercial Ir / C in alkaline electrolyte under different electroplating conditions (different current density and electroplating time) of Examples 1, 3 to 5. It can be seen from the figure that by adjusting the electroplating conditions within a suitable range, it has better oxygen evolution reaction performance, and the performance of Example 1 is higher than that of Examples 3 to 5.
[0050] Figure 5 The NiFe@TiO2 prepared in Example 1 is 100mAcm -2 After 50 hours of long-term durability test at a current density of 2.5 Å, it can be seen from the figure that the potential change of the electrode is negligible, indicating that NiFe@TiO2 has good stability.
[0051] According to the above examples, the performance of Ni-based catalysts is better than that of non-electroplated catalysts, and metal loading can effectively improve the OER activity; the performance of NiFe-based catalysts is better than that of Ni-based catalysts, with lower overpotential, better OER performance, and better stability. The synergistic effect between NiFe-based substances promotes the electrocatalytic performance of the oxygen evolution reaction.
[0052] The above-mentioned related explanations and descriptions of the embodiments are for the convenience of those skilled in the art to understand and apply the present invention. It is obvious that those familiar with the art can easily make various modifications to these contents and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above-mentioned related explanations and descriptions of the embodiments. Improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.
[0053] Matters not covered by the present invention are known technologies.
Claims
1. A method for preparing a TiO2-loaded NiFe water electrolysis catalyst, characterized in that the method comprises the following steps: (1) Treatment of titanium mesh: Select a two-electrode system, with a pretreated titanium mesh as the working electrode and a carbon rod as the counter electrode, insert them into the electrolyte, keep a constant voltage of 15-25V, and keep the time for 1 to 5h; The electrolyzed titanium mesh is heated to 450-500° C. in a mixed atmosphere and calcined for 1-3 hours to obtain a titanium mesh having TiO2 nanotubes containing oxygen vacancies grown on the surface; The electrolyte is composed of: 10-20 mL of deionized water and 80-90 mL of (CH2OH)2 are added to every 1 g of NH4F; The mixed atmosphere is hydrogen and argon; the volume ratio of the two is 5:95; (2) In a three-electrode system, a titanium mesh with TiO2 nanotubes containing oxygen vacancies grown on the surface is used as a working electrode, a carbon rod is used as a counter electrode, and a saturated calomel electrode is used as a reference electrode. The titanium mesh is immersed in an electroplating solution and deposited at a constant current of -2 to -20 mA for 10 to 60 minutes; then washed and dried to obtain a TiO2-loaded NiFe nanosheet electrocatalyst; The solutes of the electroplating solution are NiCl2·6H2O and FeCl3·6H2O, the molar ratio of Ni:Fe is 1:0.5-1.5; the total metal concentration of the electroplating solution is 0.1-0.15 mol / L; The titanium mesh is pretreated as follows: the titanium mesh is placed in C3H6O, C2H5OH and deionized water in sequence, and ultrasonically cleaned for 10-30 minutes respectively.
2. The use of the TiO2-loaded NiFe water electrolysis catalyst prepared by the method as claimed in claim 1, characterized in that it is used for electrocatalytic oxygen evolution reaction.
Citation Information
Patent Citations
Preparation method of Mg-doped NiFe-based (oxygen) hydroxide and oxygen evolution electro-catalysis application of Mg-doped NiFe-based (oxygen) hydroxide
CN114959791A